2018
DOI: 10.1111/jebm.12294
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality of trial abstracts—improved yet suboptimal: A systematic review and meta‐analysis

Abstract: The change in reporting quality of RCT abstracts is far from satisfactory, as evidenced by suboptimal post-CONSORT rates and wide CIs of effect sizes for majority of improved items. Mere publication of CONSORT-abstract guideline, without strict endorsement has failed to translate into good quality abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This finding is similar to a previous research that investigated the abstract reporting of randomized controlled trials [23]. In that review, Chhapola et al used the Consolidated Standards of Reporting Trials (CONSORT) for Abstract extension to assess the abstract reporting and their research showed insignificant change before and after the publication of the CONSORT abstract guideline [23].…”
Section: Discussionsupporting
confidence: 88%
“…This finding is similar to a previous research that investigated the abstract reporting of randomized controlled trials [23]. In that review, Chhapola et al used the Consolidated Standards of Reporting Trials (CONSORT) for Abstract extension to assess the abstract reporting and their research showed insignificant change before and after the publication of the CONSORT abstract guideline [23].…”
Section: Discussionsupporting
confidence: 88%
“…The CONSORT statement for abstracts provides authors with guidance on the necessary details and clarity required for good reporting. It is intended to improve the reporting quality of abstracts, and recently, has been used as a tool to evaluate the reporting quality of abstracts 55 , 56 , 57 , 58 , 59 . Our results show that the overall reporting quality of the abstracts of these COVID-19 RCTs is far from satisfactory, with adherence of reports to the CONSORT items ranging from 2.5% to 97.5%.…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines also recommended the use of structured format in the RCT abstracts. It has been recently reported that the quality of RCT abstracts remains suboptimal ( 4 ). Furthermore, the quality of RCT abstracts in leading dentistry journals has been documented to be suboptimal ( 5 ).…”
Section: Introductionmentioning
confidence: 99%